2007
DOI: 10.1007/s00428-007-0433-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of WT1 expression in ovarian cancer: a possible accelerator of tumor progression in serous adenocarcinoma

Abstract: Recently, oncogenic potential of the WT1 gene has been proposed in some human solid tumors and leukemias. Although previous studies have shown the frequent expression of the WT1 protein in ovarian serous adenocarcinomas (OSAs), its clinicopathologic significance is still unclear. We immunohistochemically examined the expression status of WT1 in 119 OSAs and analyzed the correlation of the intensity of WT1 immunoreactivity with the level of WT1 mRNA expression by quantitative real-time polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 37 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…A total of 29 studies 9 11 12 13 14 15 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 with 32 datasets and 4090 patients assessing the relationship between WT1 expression and prognosis of solid tumors were initially identified ( Figure 1 ), and the details of selected studies are shown in Table 1 . Twenty-one datasets evaluated carcinoma (9 for ovarian cancer, 5 for breast cancer, 3 for non-small-cell lung cancer [NSCLC], 2 for endometrial cancer, 1 for colorectal cancer and 1 for hepatocellular carcinoma) and 11 datasets evaluated non-carcinoma (2 for soft tissue sarcoma).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 studies 9 11 12 13 14 15 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 with 32 datasets and 4090 patients assessing the relationship between WT1 expression and prognosis of solid tumors were initially identified ( Figure 1 ), and the details of selected studies are shown in Table 1 . Twenty-one datasets evaluated carcinoma (9 for ovarian cancer, 5 for breast cancer, 3 for non-small-cell lung cancer [NSCLC], 2 for endometrial cancer, 1 for colorectal cancer and 1 for hepatocellular carcinoma) and 11 datasets evaluated non-carcinoma (2 for soft tissue sarcoma).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on Bcl2 in relation to prognosis are not uniform. Some studies have failed to demonstrate any significant correlation with survival [57]. On the other hand few studies have shown high levels of Bcl2 expression to be associated with lower chances of response to chemotherapy and a shorter survival [58, 59].…”
Section: Discussionmentioning
confidence: 99%
“…3 At the molecular level, high-grade ovarian serous carcinomas are genetically unstable and frequently have TP53 mutations, loss of BRCA1 or BRCA2 function, and/or amplification of oncogenes such as PRKCI, NOTCH3, EGFR, HER2, c-MYC and WT1 along with activation of several signaling pathways including ras/raf/MAP kinase and PI3 kinase/Akt pathways. 47 Low levels or altered expression of apoptosis-regulating proteins such as Bcl-2, BAX, survivin and RhoB are also reported in these tumors. 4, 8, 9 Reports suggest that in ovarian cancer, there is enhanced angiogenic-signaling pathway and a higher expression of PDGFRα, PDGFRβ and c-kit with autocrine or paracrine stimulation of the receptors by their respective ligands.…”
Section: Introductionmentioning
confidence: 99%